Approaching physical preparation for youth team-sports players - Gamble, P. (Strength and Conditioning Journal, 2008)
The benefits of physical preparation in young athletes are becoming widely accepted. This article examines the need for different aspects of physical preparation for young athletes competing in organized team sports. it further attempts to define what constitutes appropriate strength training, metabolic conditioning and neuromuscular training for young team-sports players at different phases of growth and maturation.